Compound Heterozygosity for KLF1 Mutations Causing Hemolytic Anemia in Children: A Case Report and Literature Review - Xu, Linlin; Zhu, Dina; Zhang, Yanxia; Liang, Guanxia; Liang, Min; Wei, Xiaofeng; Feng, Xiaoqing; Wu, Xuedong; Shang, Xuan (Frontiers in Genetics, 2021)
Background: Anemia is one of the most common diseases affecting children worldwide. Hereditary forms of anemia due to gene mutations are difficult to diagnose only rely on clinical manifestations. In regions with high prevalence of thalassemia such as southern China, pediatric patients with a hereditary hemolytic anemia (HHA) phenotype are often diagnosed with β-thalassemia. However, HHA can be caused by other gene defects. Here, a case that previously diagnosed with thalassemia in a local hospital was sent to our lab for further genetic diagnosis. Preliminary molecular testing did not identify any mutations in globin genes. Methods: All blood samples were collected after inform consent had been obtain from the proband’s parents. Both clinical and genetic analysis were conducted for the patient and her family members, including clinical data collection and sequencing of the KLF1 gene. Relevant literature was reviewed, including genetically confirmed cases with well-documented clinical summaries. Results: Based on the detailed clinical data for this case, we diagnosed the patient with severe HHA. Sanger sequencing confirmed that there was a mutation on each KLF1 alleles in the proband, which is missense mutation c.892G>C (p.Ala298Pro) inherited from father and frameshift mutation c.525_526insCGGCGCC (p.Gly176Argfs*179) from mother, respectively. A summary of the KLF1 mutation spectrum and a clarification of genotype-phenotype correlation was performed through a combined analysis of the case and literature studies. Conclusions: This study corrected the misdiagnosis and identified the etiology in a Chinese patient with HHA. Identification of the disease-causing gene is important for the treatment and care of the patient and prevention of another affected childbirth in her family. In addition, this study provided insight to better distinguish HHA patients with β-thalassemia mutations from those with KLF1 mutations.